Integrating Animal Husbandry and Cultural Tourism in China: Pathways, Challenges, and Strategies for High-Quality Rural Revitalization - Chen, Yumeng; Chen, Bingyan; Yin, Shi (Global Journal of Cultural Studies, 2026)
With the in-depth implementation of the rural revitalization strategy and the rapid development of the cultural tourism industry, traditional animal husbandry is facing significant opportunities for transformation and upgrading. Integrating animal husbandry with the cultural tourism industry is not only a practical requirement for promoting supply-side structural reforms in agriculture but also an important pathway to diversify the rural economy and promote comprehensive social revitalization in farming and pastoral areas. This study approaches animal husbandry not merely as an economic or industrial activity, but as a cultural practice rooted in nomadic traditions, values, rituals, and identity. This article systematically explores the practical approaches and optimization strategies for the integrated development of China's animal husbandry and cultural tourism industries, focusing on addressing key issues in the integration process such as homogenization of business formats, short industrial chains, weak infrastructure, insufficient cultural connotation, and tightening ecological constraints. By combining multiple case analyses, policy document reviews, and field investigations, the study provides an in-depth analysis of the integration models, achievements, and bottlenecks in typical regions such as Inner Mongolia, Xinjiang, and Bashang in Hebei. The findings indicate that, although emerging business formats like ecological ranch sightseeing and livestock cultural experiences have been established, common challenges remain, including lack of brand characteristics, insufficient industrial chain extension, and lagging service systems. Strengthening top-level design, highlighting regional characteristics, extending industrial chains, deepening cultural empowerment, and promoting digital transformation are effective strategies to enhance industrial synergy and added value, achieving coordinated economic, ecological, and social benefits. Future integration should adhere to a multi-dimensional collaborative mechanism of "government guidance—market-driven—farmers and herders as the main body—technology support," promoting the industrial shift from extensive expansion toward high-quality, differentiated, and sustainable development, providing practical pathways and theoretical references for rural revitalization and agricultural modernization.